Influence of quality of sibling relationship and birth order on emerging adulthood stress - Donato, Jan Gabriel
This mixed-methods study explored siblingship in emerging adulthood as it aimed to find the differences of influences between the birth order and quality of sibling relationships among young adults and how they deal with it in emerging adulthood. A purposive sampling method was used to gather 101 participants from the students of the University of the Philippines Diliman to partake in a survey using the Emerging Adults’ Stress Inventory (Murray et al., 2020) and Emerging Adulthood Relationship with Siblings Scale (Jensen et al., 2022). Nine participants consisted of the interview to explore siblingship and dealing with stress. Quantitative data was analyzed through the Kruskal-Wallis test and post-hoc pairwise comparisons to determine significant differences between the groups of variables while thematic analysis was utilized for the qualitative data to find emerging themes. Results indicate no significant difference in emerging adulthood stress across the birth orders. Overall quality of sibling relationships among the first-borns (x̄ = 3.78), middle-borns (x̄ = 4.02), and last-borns (x̄ = 3.82) had positively high levels. Differences were found among middle-borns and last-borns for qualities of ill-wishes (p = 0.040) and closeness (p = 0.013) among sibling relationships while higher levels of quality of sibling relationships observed less stress in aspects of family/home life (p = 0.015), future uncertainty (p = 0.033), and peer/friend relationships (p = 0.029). Young adults deal with stress in different ways with older siblings acting as role models and sources of advice while younger siblings offer simple forms of support while engaging in maladaptive coping strategies. These findings conclude the importance of quality of siblingship and birth order experiences with how stress is perceived and dealt with in emerging adulthood in the context of Filipinos.